Green Space Management for urban well-being and landscape quality:: Annaba case - CHAOUI , Salah (Journal of Human Sciences, 2023)
Annaba is experiencing strong and rapid demographic and spatial growth combined with the various spectra of pollution threatening human health and the environment. Its shrinking Green Spaces are below standards. They should be supported in urbanization operations for their preservation and the creation of others because greenery is a source of freshness, visual satisfaction, intellectual stimulation promoting social exchange. GS has also become an important component of the urban environment. So, by what management can we ensure urban well-being and landscape quality?